Study on physiochemical properties and the halalness of commercially marketed vinegar in Malaysia - Jamaludin, Mohd Aizat; Md Amin, Nur Alifah; Ahmad Fadzillah, Nurrulhidayah; Muflih, Betania Kartika; Othman, Rashidi; Abdullah Sani, Muhammad Shirwan; Ramli, Mohd Anuar (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
Vinegar is very popular as traditional ingredient for cooking, pickling, and preservation. It is made from sugar or starch by an alcoholic and acetous fermentation and produces ethanol as a by-product. Alcohol is prohibited to be consumed for Muslim or used as ingredient if it is exceeding the allowable limit as stated by Islamic Council in Malaysia. According to Fatwa Committee National Council of Islamic Religious Affairs Malaysia, natural occurrences of ethanol in food products are acceptable if the ethanol contents are less than 1% in beverages and 0.5% for flavoring or coloring substances for the purpose of stabilization. On the other hand, for specific vinegar product, as stated by Malaysian Food Act and Regulation, acetic acid content must be at least 4%. According to FAO/WHO, a product is to be labelled as vinegar if the acetic acid content is 6% and with a maximum residual alcohol content of 0.5%v/v for wine vinegar and 1%v/v for other vinegars. This study investigated the physiochemical properties of the vinegar from different sources of raw materials. Total solubility (TA) by using Brix method, pH, and alcohol and acetic acid content by GC-TOF/MS of 12 commercial vinegars from Malaysia and abroad were studied. The result shown that for pH value of commercial vinegar are ranged from 2.51-3.14°Brix from 2.10-40.73°Brix, acetic acid is ranged from 0.0253-0.1276% and ethanol content from 0-0.5911%. Thus, this study will come out with the clear observation on ethanol content in fermented product which is vinegar in order to categories the halalness of the product that available in Malaysia market especially the ones that are produced internationally. Lastly, as shown by the profiling study, vinegar that are imported internationally may contain some amount of alcohol in contrast with the one that locally produced in Malaysia and has Halal certification.